Revitalizing the Method of Repetition in the Recitation of the Qur'an - Muhamad Ali Anwar (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
Al Quran is the word of God, which is worth a miracle, which was revealed to the closing of the Prophets and Apostles. One of the wonders is one of the books that was recited continuously without ever stopping from the beginning announced, also a worthy reward for memorizing the Koran, so do not be surprised if Muslims race to learn it. One of the critical efforts in remembering is the method used, there are a lot of memorization methods, to improve the quality of memorization of the Qur’an, repetition is one of the essential ways to facilitate memorization that is already owned. Thus, the hope to have quality rote learning will be achieved. In the research resulted: memorization of Al-qur’an students become smoother, student becomes more disciplined with the implementation of repetition schedules, the results of the quality of memorization of these students can be seen during weekly Repetition activities, namely every Friday; when students recite their memorization by one juz on average, they are able and fluent in their memorization, students become more useful in their time.Al-Quran ialah kalam Allah yang bernilai mukjizat, yang diturunkan kepada penutup para Nabi dan Rasul. Salah satu kemukjizatannya adalah salah satu kitab yang dibacakan terus menerus tanpa pernah berhenti dari sejak awal diturunkan, juga pahala yang tanpa henti bagi penghafal Al Quran, sehingga tidak heran jika umat Islam berlomba-lomba menghafalkannya. Salah satu upaya penting dalam menghafal adalah metode yang digunakan, ada banyak sekali metode menghafal, untuk meningkatkan kualitas hafalan Al Quran, muroja’ah menjadi salah satu metode yang sangat penting guna memperlancar hafalan yang telah dimiliki. Dengan demikian, harapan untuk memiliki hafalah yang berkualitas akan tercapai. Dalam penelitian dihasilkan: hafalan Al Quran santri menjadi lebih lancar, santri menjadi lebih disiplin dengan diterapkannya jadwal-jadwal muroja’ah, hasil kualitas hafalan santri ini bisa dilihat saat kegiatan muroja’ah pekanan yaitu setiap hari jum’at, saat santri melafalkan hafalannya satu juz rata-rata mampu dan lancar dalam hafalannya, santri menjadi lebih bermanfaat waktu-waktunya.